2019
DOI: 10.1371/journal.pone.0216246
|View full text |Cite
|
Sign up to set email alerts
|

Yeast species isolated from Texas High Plains vineyards and dynamics during spontaneous fermentations of Tempranillo grapes

Abstract: Vineyards and grape musts harbor complex locally specific microbial communities, among which yeast species can be responsible of spontaneous alcoholic fermentation. Although relying on indigenous yeast can be a risk for winemaking, local yeast diversity is associated with complexity and stronger identity of the wine produced, compared to inoculated alcoholic fermentation with commercial yeast strains. In this context, the main yeast species present on grapes, leaves and soils of Tempranillo and Cabernet Sauvig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Settanni et al [57] reported high counts of yeasts in grapes from the Marsala wine area (Italy) with values that ranged from 3.54 to 6.92 log 10 CFU/g, which agreed with the yeast population found in the present work. In contrast, lower counts (10 2 to 10 4 log 10 CFU/g) of yeasts in healthy grapes from Texas (USA) were reported by Bougreau et al [58]. Damaged grapes gave higher counts of yeasts than healthy grapes from Attica (Greece), according to Nisiotou and Nychas [59] and from Trento, Italy [60]; these are in contrast with the results obtained in the present work.…”
Section: Discussioncontrasting
confidence: 98%
“…Settanni et al [57] reported high counts of yeasts in grapes from the Marsala wine area (Italy) with values that ranged from 3.54 to 6.92 log 10 CFU/g, which agreed with the yeast population found in the present work. In contrast, lower counts (10 2 to 10 4 log 10 CFU/g) of yeasts in healthy grapes from Texas (USA) were reported by Bougreau et al [58]. Damaged grapes gave higher counts of yeasts than healthy grapes from Attica (Greece), according to Nisiotou and Nychas [59] and from Trento, Italy [60]; these are in contrast with the results obtained in the present work.…”
Section: Discussioncontrasting
confidence: 98%
“…This study aligns with the increasing demand for indigenous S. cerevisiae isolates that are representative of a specific oenological area 62 , with particular wineries increasingly selecting yeasts within their vineyard for specific characteristics and suitability to local grape varieties 63,64 . Extensive studies of spontaneous fermentations in Italy 65 , Spain 18,66 , USA 67 and Canada 68 (including studies specifically of the genetic diversity of Saccharomyces cerevisiae in different wine-producing regions 36,69,70 ) are validated or partly motivated by reports 71 www.nature.com/scientificreports/ of a significant correlation between the region from where the strains were isolated and the aroma profile of the resulting wines. In this study, four non-Saccharomyces yeasts (Metschnikowia pulcherrima, Lachancea thermotolerans, Hanseniaspora uvarum and Torulaspora delbrueckii) were isolated from Negro Saurí grapes and must, based on their colony morphology and subsequent ITS sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The strive for more volatile aromas has spurred the search for alternative yeasts and renewed the interest in spontaneous fermentations [26]. Yet, due to the unpredictable and inconsistent outcomes of spontaneous fermentations, the development of improved starter cultures or consortia may provide better alternatives [27,28].…”
Section: Discussionmentioning
confidence: 99%